Field demonstration of multi-domain software-defined transport networking with multi-controller collaboration for data center interconnection [Invited] - Yu, Yiming; Zhang, Jie; Zhao, Yongli; Lin, Yi; Han, Jianrui; Zheng, Haomian; Cui, Yadi; Xiao, Minglu; Li, Hui; Peng, Yang; Ji, Yuefeng; Yang, Haifeng (Journal of optical communications and networking, 2015)
Software-defined networking (SDN) with optical transport techniques enables network operators and data center (DC) operators to provide their resources dynamically on user's demands while minimizing operating and capital expenditure. Current multi-domain networking techniques mainly rely on the path-computing element, while SDN has shown considerable potential for this inevitable issue. The first field demonstration of multi-domain software-defined transport networking (SDTN) without global topology information is detailed in this paper. A multi-controller collaboration framework and three schemes, a controller-driven scheme (ConDS), a cloud-driven scheme (ClDS), and a ClDS with dynamic optimization (ClDS-DO), for datacenter interconnection based on SDTN are demonstrated via field networks. We also extend the OpenFlow protocol and design the Java-Script Object Notation application programming interface to support this framework. Multi-domain lightpaths are automatically provided with limited signaling latency. The blocking performances of the proposed schemes are estimated, and the ClDS-DO has the best performance approaching the optimal boundary.